Anti-diabetic effects of marine natural products through redox modulation via Nrf2/HO-1 cytoprotective pathways - Nisar, Muhammad Farrukh; Li, Mingxi; Xu, Jialin; Wan, Chunpeng (Frontiers in Marine Science, 2024)
Diabetes mellitus (DM), a major global health concern is a chronic metabolic disorder. Bioactive compounds sourced from numerous marine natural products recently have drawn attention as novel therapeutic approaches. Considering these chemicals and their role in cellular redox modulation by involving nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway, current study attempts to highlight their anti-diabetic effects and molecular mechanisms involved. Reactive oxygen species (ROS) mediated oxidative stress, inflammation, and cellular damage are linked to most of human pathologies specifically DM.Nrf2/HO-1 pathway is a key defensive mechanisms developed by the cells to combat ROS burst. Marine natural compounds have strong pharmacological potential in triggering cellular antioxidant defense mechanisms by declining oxidative damage and inflammations linked with DM. Special focus on how marine natural products potentially alleviate DM specifically type 2 diabetes (T2D) and its related issues. The literature was thoroughly analyzed to open a discussion about specific marine compounds and their well-established anti-diabetic effects to elucidate possible therapeutic applications. Furthermore, opportunities, pros and cons of us-ing these marine bioactive compounds as complementary treatment for DM also discussed.The diverse characteristics of marine natural products, specifically with regard to redox control, offer promising opportunities for drug discovery and therapeutic interventions in clinical trials.